A methodological review of qualitative research syntheses in CALL: The state-of-the-art. (December 2021) - Chong, Sin Wang; Reinders, Hayo
Abstract: Qualitative research in computer-assisted language learning (CALL) has received more attention recently, most evidently from the publications of two special issues on qualitative research in CALL by CALICO Journal (2015) and Language Learning & Technology (2018). The inherent strength of qualitative studies in CALL is that they celebrate depth of interpretation by focusing on specific contexts and a small number of participants. Yet this strength can sometimes be perceived as a limitation when transferability and applicability of findings are considered. However, this potential shortcoming can be overcome when findings of multiple studies are meaningfully synthesised, for example, in a qualitative research synthesis (QRS). QRS is a relatively new form of research synthesis in CALL which systematically summarises qualitative findings guided by research questions and a predetermined research protocol. To report current methodological practices and identify areas of strengths and weaknesses, this exploratory review analyses the methodological sections of 16 QRS in CALL using a recent, CALL-based QRS methodological framework comprising seven stages (Chong & Plonsky, 2021). Findings reported include implementation of the seven methodological stages, and convergent and divergent methodological practices. Suggestions, especially about qualitative data extraction and synthesis, are made in light of the findings.